Respondents wise Status of Non-Governmental Organizations (NGOs) of Karnali Zone Nepal - Mahat, Kushendra Bahadur; Pokharel, Bihari Binod (Journal of Advanced Academic Research, 2017)
Non-Governmental Organizations (NGOs) have been promoted in the development activities in Nepal since the restoration of democracy in 1990. NGOs have been recognized as one of the development facilitator institutions in Karnali Zone. The objective of this study was focused to identify the status of Non-Governmental Organizations (NGOs) on the basis of its structure, environment, values and Impact. The study had adopted the civil society index as a theoretical tool of study. Randomly in total 562 respondents were selected from five districts of Karnali zone. The findings of ANOVA showed that there was a significant difference between respondents in the structure of NGOs in P=0.007 significant level at 95% confidence interval. But other three components environment, values and impact were not significantly difference. It could be assumed that because of the geographical differences, involvement of human resources, basic infrastructure, access on communication and technologies and perception on NGOs activities are the major factors which made the perceptual difference among the respondents in structure of NGOs. Similarly, contribution of NGO in promotion of political awareness, transparency of their work and empowering citizenship were more or less in the same level in all five districts so response of participants became similar in environment, values and impact of NGOs. It is necessary to identify the locally reliable and related indicators of NGO to assess the NGO's status and their performance.